Foreign language education in portuguese higher education institutions: the state of play - Ceia, Carlos (2017)
Over the last 15 to 20 years, changes in foreign language teaching policies in Portuguese higher education institutions (HEIs) have been subject to little discussion and less inter-institutional dialogue. Each institution has absorbed different European directives, and more specifically adapted its context in response to the Bologna Process, according to its own interpretation leading to widespread distortion across foreign language teaching curricula. While demand for foreign language courses remains high in Portuguese HEIs there has been little formal research and scarce funding available for projects related to introducing innovative practices and materials. This paper provides a critical reading of the current state of play in this crucial sphere of higher education in Portugal.